The impact of influencer marketing in the tourism industry: A digital marketing perspective - Md. Asaduzzaman Babu; Hafsa Akter Urmi; Abzal Hosen Tofayel; Md. Mehedul Islam Sabuj; Md Tamjid Ul Alam (PLoS ONE, 2025)
This study aims to examine how influencer marketing shapes tourists’ perceptions and purchase intentions in the tourism sector of Bangladesh. Specifically, it examines the impact of word of mouth, content characteristics, consumer trust, emotional connection, and brand awareness on consumer perception, as well as how these perceptions influence purchase intention within a digital marketing context. A quantitative, cross-sectional design was employed, utilizing a structured online questionnaire distributed to active social media users who follow travel influencers. Data were collected from 400 respondents through non-probability purposive sampling, representing individuals familiar with influencer-generated travel content. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed hypotheses and evaluate both measurement and structural models. Results revealed that word of mouth (β = 0.269, p < 0.001), content characteristics (β = 0.152, p < 0.05), consumer trust (β = 0.207, p < 0.05), emotional connection (β = 0.170, p < 0.05), and brand awareness (β = 0.200, p < 0.001) significantly influence consumer perception. In turn, consumer perception strongly predicts purchase intention (β = 0.561, p < 0.001). All five influencer-related factors; word of mouth, content characteristics, trust, emotional connection, and brand awareness significantly influence consumer perception, which in turn strongly predicts purchase intention. Among these, trust, word of mouth, and content quality were found to be the most influential predictors of success. The findings confirm that credible and engaging influencer communication enhances tourists’ perceptions and motivates travel-related purchasing behavior. The study provides actionable insights for tourism marketers and policymakers, emphasizing the importance of authenticity, message quality, and trust-building in influencer collaborations. It also highlights the need for integrating influencer campaigns into broader destination branding strategies. This research contributes theoretically by integrating Social Influence Theory and Source Credibility Theory into a single model. It provides new empirical evidence from an emerging tourism market (Bangladesh), expanding cross-cultural understanding of influencer marketing’s role in shaping consumer behavior in digital tourism.